Abuso financeiro intrafamiliar à pessoa idosa - Rodrigues, Raimunda Carvalho Lemos (Universidade Federal do Tocantins, 2022)
The present TCC - Course Conclusion Paper aimed to discuss Financial Intrafamily Violence against the elderly in the city of Miracema do Tocantins (TO), besides presenting other forms of abuse, such as physical and psychological. It also aimed to understand how to configure the cases of financial abuse to the elderly in the city of Miracema do Tocantins (TO). As a specific objective, we sought to know the profile of elderly victims of this type of violence. For this, we used theoretical contributions that discuss the concept of Old, Elderly and Third Age, Vulnerability, Family and Elderly, Violence Intrafamily and, finally, the Statute of the Elderly. From this perspective, the National Policy for the Elderly provides Law No. 8,842, of January 1994, created to ensure the social rights of the elderly. Other bibliographic references also served as subsidies for this study. The qualitative research method was used through interviews with the CREAS team of Miracema do Tocantins - TO. The results revealed that some elderly people have their rights violated. Finally, some final considerations are presented regarding the work performed.